Preventive acetaminophen reduces postoperative opioid consumption, vomiting, and pain scores after surgery: systematic review and meta-analysis - Doleman, Brett; Read, David; Lund, Jonathan N.; Williams, John P. (Lippincott Williams & Wilkins, 2015)
Background and Objectives: Preventive analgesia has been proposed as a potential strategy to reduce postoperative pain. However, there is currently no review that focuses on acetaminophen for preventive analgesia.